A prospective study of oral estrogen versus transdermal estrogen (gel) for hormone replacement frozen embryo transfer cycles. (3rd June 2021) - Garimella, Sita; Karunakaran, Sandeep; Gedela, Durga Rao
Abstract: Aim: This study was done to compare the efficacy of transdermal estrogen (gel) to oral estradiol in hormone replacement frozen embryo transfer cycles (HR- FET). Materials and methods: This was a prospective study conducted between March 2019 and December 2019. We included 294 HR FET cycles: 156 cycles using oral estrogen tablets (oral group) and 138 cycles using transdermal gel (17 beta estradiol 0.06% w/w) (gel group). Primary objective of this study was to compare endometrial thickness (ET) on the day of progesterone start between the two groups. Our secondary objective was to compare implantation rates (IR), clinical pregnancy rates (CPR), miscarriage rates (MR), duration of estrogen administration, estradiol (E2) levels before the start of progesterone, cycle cancellation rates, patient satisfaction score and undesirable side effects between both the groups. Results: There was no significant difference in the ET, IR, CPR, MR and duration of E2 administration and cycle cancellation rates between both the groups. Patient satisfaction score was significantly higher (8.02 ± 1.07 vs 6.96 ± 0.99 p  < .01) and side effects were significantly lower (18.1% vs 55.1%, p ≤.01), in the gel group compared to the oral group. Conclusion: This study concluded that transdermal estrogen (gel) is equally efficacious as oral estrogen in HR FET cycles with transdermal gel having an added benefit of better patient comfort with less side effects and better safety profile.